Training of Trainers (TOT) Pengembangan Soft Skill Guru, Melalui Workshop Implementasi Kurikulum Merdeka di Yayasan Ar-Rosyad Kediri - Moh. Irfan Burhani; Moh. Zainal Fanani; Afifah Meilani Zulfa; Ahmad Yusuf Syaifulloh; Sahrul Kirom (Fakultas Tarbiyah dan Ilmu Keguruan UIN Syekh Wasil Kediri, 2025)
This community service activity (PkM) was carried out with the main objective of optimizing readiness, improving competence, and strengthening the skills and mindset of teachers under the auspices of the Ar-Rosyad Islamic Boarding School Foundation in Kediri Regency in facing the demands of implementing the Merdeka Curriculum. The context of the PkM implementation was motivated by findings that revealed problems such as teachers' lack of access to continuous training, conceptual confusion regarding the Merdeka Curriculum, and the lack of infrastructure and digital facilities needed to support the new learning paradigm. This PkM is a strategic response by higher education institutions to support learning recovery (learning loss) after the pandemic and adaptation to the demands of 21st-century education in madrasahs.The method used in this community service program is the Learning Community approach integrated with the Training of Trainers (TOT) mentoring model. The subjects of the activity were 50 teachers from various levels of education, including Raudhatul Athfal (RA), Madrasah Ibtidaiyah (MI), Madrasah Tsanawiyah (MTs), and Madrasah Aliyah (MA) under the Ar-Rosyad Balong Ringinrejo Kediri Islamic Boarding School Foundation. The Learning Community approach aims to create a collaborative ecosystem so that teachers can share knowledge and solve implementation problems independently. Meanwhile, the TOT model focuses on developing core teachers into trainers who are able to duplicate their expertise to their peers, ensuring the sustainability of the program.The results of these workshops and mentoring sessions show a significant improvement in teachers' understanding of the philosophy and concepts of the Merdeka Curriculum. In practical terms, teachers have been able to develop essential teaching tools, such as the Education Unit Operational Curriculum (KOSP), formulate Learning Objective Flow (ATP) from Learning Outcomes (CP), and develop Teaching Modules that are integrated with the Pancasila Student Profile. The TOT training has successfully changed teachers' mindsets to be student-centered and created the institutional capacity of the foundation to manage curriculum changes independently.